Analisis Persepsi Konsumen Pada Penggunaan Layanan LinkAja Syariah di Kota Bekasi - Yulia Shyfa Pertiwi; Fitri Yetti (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
This study was conducted to find out how consumers perceive LinkAja Syariah users by analyzing stimulus factors and individual factors in using LinkAja Syariah in Bekasi City. This study uses descriptive qualitative research methods. Data collection techniques used are interviews and documentation. Data analysis techniques used are data reduction, data presentation and conclusions. Based on the results of the research analysis, it was concluded that consumer perceptions of the use of the LinkAja Syariah service by analyzing the stimulus factors in the three features were that the LinkAja Syariah service had a simple and easy-to-understand appearance so that it was easy to use and the size of the application was small. Then on the individual factor in the three features, the LinkAja Syariah service collaborates with many companies or institutions so that the LinkAja Syariah service application is integrated with the application of the company or institution, there are minimal obstacles, although there are some obstacles that occur by LinkAja Syariah users.